DAMPAK PENGGANDA OUTPUT SEKTOR INDUSTRI KUNCI TERHADAP PEREKONOMIAN KALIMANTAN SELATAN - Arief Hidayat; M Handry Imansyah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study focuses on estimating the output multiplier impact of 12 main manufacturing industry subsectors in South Kalimantan Province. Using the Miyazawa Input-Output Model framework, the output multiplier value for each subsector is obtained, which reflects the increase in total output per Rp 1 million increase in final demand. The identification results indicate that the Metal Goods, Computers, Electronics, Optics, and Electrical Equipment subsector (2.504) has the highest multiplier, followed by Furniture (2.317) and Textiles & Apparel (2.006). Conversely, the Chemicals, Pharmaceuticals, and Traditional Medicines subsector (1.254) and Transportation Equipment (1.268) show the lowest multipliers. These findings provide an empirical basis for prioritizing subsectors with the greatest economic chain effects in sustainable industrialization policies in South Kalimantan.